Primary leiomyosarcoma of the bone: a case report - Ala Abu-Dayeh; Samir Alhyassat (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Primary leiomyosarcoma of the bone is rare. Histologically, it resembles leiomyosarcoma of soft tissue. Given the rarity of this entity, its diagnosis should be made only after clinical studies and workup have excluded metastasis from other sites. Herein, we describe an additional case of primary bone leiomyosarcoma. We report a 32-year-old female patient, who presented with right knee pain and was found to have a right distal femur mass by imaging studies. Biopsy showed a neoplasm composed of fascicles of spindle cells, arranged in different patterns, with significant pleomorphism. The tumor cells were positive for smooth muscle actin, focally positive for desmin and H-caldesmon. No other masses in the body were detected by imaging studies. The diagnosis of leiomyosarcoma of the bone was rendered. Given the broad diagnostic differential of primary bone leiomyosarcoma, it is important to be aware of this rare bone tumor phenotype and of its histomorphologic and immunohistochemical features for an accurate diagnosis.